The scientific focus of adaptive physical culture in contemporary publication content - Parfenova, L.A. (Theory and Practice of Physical Culture, 2025)
Objective of the study is to identify the main areas of scientific research on adaptive physical culture (APC) in the context of publications in the journal Teoriya i Praktika Fizicheskoy Kultury (2020-2024) and to outline the scientific and practical prospects for the development of the industry. Methods and structure of the study. Review and systematisation of publications addressing APC issues based on selected categories and analysis criteria, processing of the data obtained using mathematical and descriptive statistics. Results and conclusions. A total of 232 articles on APC were identified, authored by 572 scientists (60.6% women, 24% doctors of science, 53.7% candidates of science). Researchers from Saint Petersburg, Moscow, Kazan, and Perm are the most active. Adaptive physical education (APE) (93 articles) dominates, especially for students with health disabilities (43 articles) and children with disabilities in special education (34 articles). Also significant are the issues of adaptive sports (65) and physical rehabilitation (45). Little attention is paid to creative and extreme practices (1) and adaptive motor recreation (2). Research on inclusion and the GTO physical fitness test for people with disabilities is relevant. Research on people with musculoskeletal disorders (44 articles) and somatic and intellectual disabilities (25 articles each) predominates. The results of pedagogical experiments are presented in 77.2% of the works. The most cited articles are on the professional training of specialists in adaptive physical culture and adaptive physical education in special medical groups. Over the past 5 years, 2 doctors and 16 candidates of pedagogical sciences in the field of physical culture have appeared. Recommendations have been made to update the editorial policy regarding physical culture and adaptive sports.